2008
DOI: 10.3198/jpr2007.04.0197crc
|View full text |Cite
|
Sign up to set email alerts
|

Registration of Common Bacterial Blight, Rust and Bean Common Mosaic Resistant Great Northern Common Bean Germplasm Line ABC‐Weihing

Abstract: Great northern common bean (Phaseolus vulgaris L.) germplasm line ABC‐Weihing (Reg. No. GP‐246, PI 647964) was developed by the University of Nebraska Agricultural Research Division in cooperation with USDA‐ARS and released in 2006. This line, tested as NE1‐05‐4, was bred specifically for enhanced resistance to common bacterial blight (CBB), a major seed borne disease of common bean caused by the bacterium Xanthomonas campestris pv. phaseoli (Smith) Dye (Xcp). ABC‐Weihing is a great northern BC5F3:6 line obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 8 publications
(6 reference statements)
0
19
0
Order By: Relevance
“…Although O'Boyle et al (2007) observed a slight yield penalty of 7% in one of two environments for black bean lines developed with the SU91 marker, many high‐yielding lines with SU91 were also observed. The ABC Weihing great northern bean (Mutlu et al, 2008) with SU91 derived by five backcrosses had similar yield to the recurrent parent Weihing (Coyne et al, 2000), 5177 versus 5107 kg ha −1 , in a recent CBB‐free field trial (unpublished) that we conducted in Othello, WA, in 2015. Mutlu et al (2005b) observed that pinto bean ABCP‐8 with SU91 developed from backcrossing had higher yield than the recurrent parent ‘Chase’ pinto in nondiseased trials (Coyne et al, 1994).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Although O'Boyle et al (2007) observed a slight yield penalty of 7% in one of two environments for black bean lines developed with the SU91 marker, many high‐yielding lines with SU91 were also observed. The ABC Weihing great northern bean (Mutlu et al, 2008) with SU91 derived by five backcrosses had similar yield to the recurrent parent Weihing (Coyne et al, 2000), 5177 versus 5107 kg ha −1 , in a recent CBB‐free field trial (unpublished) that we conducted in Othello, WA, in 2015. Mutlu et al (2005b) observed that pinto bean ABCP‐8 with SU91 developed from backcrossing had higher yield than the recurrent parent ‘Chase’ pinto in nondiseased trials (Coyne et al, 1994).…”
Section: Resultsmentioning
confidence: 94%
“…The identification of major quantitative trait loci (QTL) controlling resistance to CBB (reviewed by Miklas et al, 2006a; Miklas and Singh, 2007; Viteri et al, 2014b; Singh and Miklas, 2015) has facilitated marker‐assisted breeding for higher levels of CBB resistance into better‐adapted and higher‐yielding dry bean lines (Miklas et al, 2000; Mutlu et al, 2005a). The QTL and linked markers, ultimately derived from great northern landrace and tepary bean, have been used to develop dry bean germplasm lines USDK‐CBB‐15 (Miklas et al, 2006b), USWK‐CBB‐17 (Miklas et al, 2006c), ABCP‐8 (Mutlu et al, 2005b), USCR‐CBB‐20 (Miklas et al, 2011), and cultivars such as ‘ABC‐Weihing’ (Mutlu et al, 2008). Generally, the markers tightly linked with the QTL have been used for marker‐assisted backcrossing and early‐generation selection of the resistance genes, which is then followed up by traditional phenotypic selection using pathogen challenge in the greenhouse and field during later generations (reviewed by Viteri et al, 2014b; Singh and Miklas, 2015).…”
mentioning
confidence: 99%
“…Low soil fertility tolerance Derived from germplasm accessions, landraces and improved lines Singh et al (2003a, b) Low soil fertility and drought tolerance Beebe et al (2008) Multiple disease and pest resistance Angular leaf spot, anthracnose, Common bacterial blight, bean Common mosaic virus, Bean golden mosaic virus and leafhopper resistance Singh et al (1998) Common bacterial blight, rust and Bean common mosaic virus resistance Mutlu et al (2005Mutlu et al ( , 2008 Pyramided rust, Bean common mosaic virus and Bean common necrotic mosaic resistance genes producing high levels of resistance Pastor-Corrales (2003) and PastorCorrales et al (2007) Multiple virus resistance Scully et al (1995) Bean common mosaic virus, Beet curly top virus and root rot resistance Silbernagel et al (1998) Smith et al (2007 many important bean diseases have been identified and used in cultivar development programs (Miklas et al 2006b;Beaver et al 2003). However, breeders also need information from plant pathologists concerning the virulence patterns of the pathogens in order to most effectively deploy disease resistance genes .…”
Section: Resistance To Biotic Constraintsmentioning
confidence: 99%
“…The objective of the present work was to evaluate the response to CBB of five traditional bean varieties (Tondino bianco, Verdolino, Cannellino, Tabacchino and Ciuoto) of the FS variety pool, in comparison to four available resistant bean breeding lines (VAX-4, USDK-CBB-15, ABC-Wiehing and USCR-CBB-20) (Singh et al 2001;Miklas et al 2006Miklas et al , 2011Mutlu et al 2008). Aliquots of bacterial suspensions of the highly virulent Xap and Xapf strains were inoculated into the first trifoliate mesophyll of bean plants (Lo Cantore et al 2010a).…”
Section: Response Of Fagioli DI Sarconi Varieties To Cbbmentioning
confidence: 99%